Experimental and Numerical Study in Dynamic Compaction of Weakly-Cohesive Soils - Carmen Nicoleta Debeleac; Andrei Buraga; Silviu Marian Nastac (Applied Sciences)
The rheological modeling of soil–drum interaction in the vibratory compaction process is a complex process. This paper aims to describe the behavior of soil–drum interaction through lumped parameter modeling. The amplitude of the vertical motion is evaluated for dynamic conditions using the rheological models (generalized and advanced Kelvin–Voigt-based models) and compared with the experimental results obtained from weakly cohesive soil compaction. Different modeling approaches are considered, and the results reveal that the properties of the soil as input play a vital role in the accuracy of the modeling.